Agricultural extension in times of crisis and emergent threats: Effectiveness of a fall armyworm information intervention in Myanmar - Goeb, Joseph; Maredia, Mywish K.; Herrington, Caitlin; Zu, A Myint (International Food Policy Research Institute, 2023)
Agricultural extension can have important impacts on vulnerable populations by increasing food production, which improves both rural incomes and urban food security. Yet, crises induced by violent conflict or disease outbreaks can sever the connections between extension agents and farmers. Understanding how agricultural extension systems can safely and effectively reach farmers in times of crisis could help stabilize agri-food systems in fragile states. In the context of COVID-19, a military coup, and an emergent threat of fall armyworm in Myanmar, this paper uses a randomized controlled trial to test the effectiveness of two cellphone-based extension interventions – a direct-to-farmer and a lead farmer intervention – for fall armyworm control in maize. Despite low compliance, both interventions caused knowledge improvements. However, damage control estimates show that the lead-farmer group used pesticides most effectively. Similar cellphone-based lead-farmer programs could be an effective tool in fragile states and when faced with emergent threats to agriculture.